Stress and Anxiety Level of Nursing Students in Facing Practical Exam During Pandemic 19 - Rozhalia Uji Kusumaningtyas; Sri Suparti (UM Purwokerto Press, 2022)
Background: Persons enrolled in nursing school are prepared to advance into nursing in the future. Before engaging in nursing clinical practice in hospitals, nursing students are required to be able to advance their competence in the lab. Students studying nursing experience stress and anxiety due to the switch from online to offline lab learning. Objective: To determine and identify nursing students’ stress and anxiety levels in facing practical exams. Method: This study is cross-sectional quantitative descriptive research. A total of 190 nursing students from the second semester at Universitas Muhammadiyah Purwokerto participated in the study as the sample on April 20, 2022. The DASS-21 questionnaire for sub-stress and anxiety was modified for the research instrument. A univariate data analysis with frequency distribution was used as the data analysis. Results: The findings revealed that 115 (60.5%) nursing students reported normal stress, 32 (16.8%) mild stress, 23 (12.1%) moderate stress, 18 (9.5%) severe stress, and 2 (1.1%) very heavy stress. There were 32 (16.8%) students who moderate anxiety, 26 (13.7%) severe anxiety, and 28 (14.7%) very severe anxiety. Conclusion: Most nursing students preparing for practical exams experienced normal stress and moderate anxiety levels.